2022
DOI: 10.1101/2022.02.23.481521
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeting TRIP13 in Wilms Tumor with Nuclear Export Inhibitors

Abstract: Wilms tumor (WT) is the most common renal malignancy of childhood. Despite improvements in the overall survival, relapse occurs in ~15% of patients with favorable histology WT (FHWT). Half of these patients will succumb to their disease. Identifying novel targeted therapies in a systematic manner remains challenging in part due to the lack of faithful preclinical in vitro models. We established ten short-term patient-derived WT cell lines and characterized these models using low-coverage whole genome sequencin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Interestingly, the CRM1/XPO1 exportin has been recently identified in a screen for potential druggable targets involving TRIP13 function in Wilms tumor derived lines. Furthermore, the FDA-approved drug selinexor (KPT-330), which inhibits nuclear export, leads to suppression of TRIP13 function in these cell lines and it has been proposed as a potential therapeutic strategy for Wilms tumor patients [ 83 ]. In sum, all these observations underscore the potential relevance of Pch2/TRIP13 nucleocytoplasmic traffic in the multiple biological processes impacted by this protein family.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the CRM1/XPO1 exportin has been recently identified in a screen for potential druggable targets involving TRIP13 function in Wilms tumor derived lines. Furthermore, the FDA-approved drug selinexor (KPT-330), which inhibits nuclear export, leads to suppression of TRIP13 function in these cell lines and it has been proposed as a potential therapeutic strategy for Wilms tumor patients [ 83 ]. In sum, all these observations underscore the potential relevance of Pch2/TRIP13 nucleocytoplasmic traffic in the multiple biological processes impacted by this protein family.…”
Section: Resultsmentioning
confidence: 99%
“…Surface proteins WT1 46 and GPC3 47 are potential therapeutic immune targets in WT and are currently being explored in immunotherapy studies NCT02789228/NCT05238792 and NCT04928677, respectively. DS‐8201a, a HER2 antibody conjugated to a topoisomerase 1 payload, and Selinexor, 48–50 an inhibitor of the nuclear pore XPO1, are two agents with promising laboratory data, which are undergoing clinical trials in other pediatric solid tumors and thus may be amenable to clinical investigations in WT. The heterogeneous genomic landscape of WT makes it challenging to identify selective inhibitors that are effective across all high‐risk WT cases; however, therapeutic vulnerabilities have been identified that could benefit particular subsets of patients; for example, CDK9 inhibitors in MLL1/ENL mutant tumors, 51 BRD4 inhibitors in MYCN‐driven tumors, 52 as well as WT with specific DNA damage response defects such as deleterious mutations in ATM via the ATR inhibitor elimusertib on NCT05071209 (PEPN2112).…”
Section: Development Of Novel Agents For Wilms Tumormentioning
confidence: 99%
“…45 Surface proteins WT1 46 and GPC3 47 are potential therapeutic immune targets in WT and are currently being explored in immunotherapy studies NCT02789228/NCT05238792 and NCT04928677, respectively. DS-8201a, a HER2 antibody conjugated to a topoisomerase 1 payload, and Selinexor, [48][49][50] an inhibitor of the nuclear pore XPO1, are two agents with promising laboratory data, which are undergoing clinical trials in other pediatric solid tumors and thus may be amenable to clinical investigations in WT.…”
Section: Development Of Novel Agents For Wilms Tumormentioning
confidence: 99%
“…Interestingly, the CRM1/ XPO1 exportin has been recently identified in a screen for potential druggable targets involving TRIP13 function in Wilms tumor derived lines. Furthermore, the FDA-approved drug selinexor (KPT-330), which inhibits nuclear export, leads to suppression of TRIP13 function in these cell lines and it has been proposed as a potential therapeutic strategy for Wilms tumor patients [83].…”
Section: Plos Geneticsmentioning
confidence: 99%